A nationwide, prospective collection of patient reported outcomes in the Cancer Registry of Norway - Ylva Maria Gjelsvik; Tom Børge Johannesen; Giske Ursin; Tor Åge Myklebust (Norsk Forening for Epidemiologi, 2022)
Background: The Cancer Registry of Norway (CRN) has collected data on all Norwegian cancer patients from health providers since 1952. To assess cancer patients' self-reported late effects and health related quality of life(HRQoL) after treatment, the CRN started collecting data on Patient Reported Outcomes (PROs) in 2020. Objectives: To present the infrastructure for the CRN's national health survey collection of PROs and describe some experiences of the first two years of data collection. Methods: In 2021, the CRN invited patients newly diagnosed with prostate cancer, breast cancer, colorectal cancer, or malignant melanoma to participate in the three-year digital health survey "Population survey on health and quality of life". Patients were invited at least 21 days after diagnosis and within 150 days of the diagnosis. A control group consisting of individuals with no history of the cancer in question was randomly drawn from the National Population Register. Descriptive statistics regarding invitations and participation are presented. Results: A total of 15 641 patients and 15 187 individuals in the control group were identified as eligible for participation in 2021. A total of 12 297 (82%) of the patients and 11 534 (76%) of the controls used one or more of the digital solutions the CRN used to distribute the surveys and received an invitation to the survey. Overall, 6 091 (47%) of the patients and 3 718 (32%) of the controls participated, with variation across the cancer types. Discussion: Self-reported late effects and HRQoL after contemporary cancer treatments can be studied among participants in these nationwide longitudinal surveys which continuously include newly diagnosed patients. The response rates at baseline are still somewhat low and vary between 41% and 51% among the cancer patients. Selection bias may be a challenge, as half of (or less) than the individuals invited in 2021, chose to participate. Conclusions: The infrastructure for a national, prospective survey collection of PROs is in place and in use. The CRN plans to analyse the representativeness and validity of the PROs data. The goals are to include PROs in surveys covering all the clinical registries at the CRN, and that the PROs collected by the CRN can be used in research and quality improvement of the health services offered to cancer patients.